Opinions of International Students on Choosing a State University in a Developing Country - Boyaci, Adnan; Oz, Yakup (Journal of International Students, 2019)
In this study, factors affecting the college choice of international students (CCIS) are investigated based on the opinions of international students at a state university (Anadolu University) in Turkey. A case study design is employed and opinions of students are analyzed in accordance with whether they are scholarship or non-scholarship students. In the findings, three main themes emerge; intent to study abroad, choosing to study in Turkey, and choosing to study at Anadolu University. These themes cover several factors affecting the CCIS. In this regard, there are no critical differences between the factors affecting the opinions of scholarship and non-scholarship students. However, some factors could differentiate in accordance with the background characteristics of the students and whether they are from high-income or non-high-income countries.